2000
DOI: 10.2136/sssaj2000.643962x
|View full text |Cite
|
Sign up to set email alerts
|

Cattle Manure Amendments Can Increase the pH of Acid Soils

Abstract: Trace metal chemistry in arid-zone field soils amended with sewage sludge: I. Fraction-groves in relation to certain soil constituents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

41
191
3
21

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 394 publications
(256 citation statements)
references
References 17 publications
41
191
3
21
Order By: Relevance
“…Many other authors reported no effect on pH (Bevacqua and Mellano, 1994;Crecchio et al, 2001;Zebarth et al, 1999). However, there are several studies that revealed either an increase of acidic soil (Hue, 1992;Whalen et al, 2000;Baziramakenga et al, 2001;Butler and Muir, 2006;Valarini et al, 2009) or a decrease (Chang et al, 1991), While increasing pH is clearly valuable in terms of improving microelement availability, lowering pH should be limited to avoid enhancing the solubility of toxic elements. In this study, we did not detect Cd, Ni or Pb and most other heavy metals such as Cr, Zn, Mn, Ba, Sr and Ti were detected at very low concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Many other authors reported no effect on pH (Bevacqua and Mellano, 1994;Crecchio et al, 2001;Zebarth et al, 1999). However, there are several studies that revealed either an increase of acidic soil (Hue, 1992;Whalen et al, 2000;Baziramakenga et al, 2001;Butler and Muir, 2006;Valarini et al, 2009) or a decrease (Chang et al, 1991), While increasing pH is clearly valuable in terms of improving microelement availability, lowering pH should be limited to avoid enhancing the solubility of toxic elements. In this study, we did not detect Cd, Ni or Pb and most other heavy metals such as Cr, Zn, Mn, Ba, Sr and Ti were detected at very low concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…However, in all layers, the soil water pH was highest in treatment DL 180, showing that this material raises the soil pH. Animal manure, as for example swine deeplitter, which is solid and has a greater percentage of dry matter than pig slurry (Table 1), is likely to have greater contents of carbonate, promoting the consumption of H + after being dissolved in the soil, which is reflected in an increase of water pH (Whalen et al, 2000;Anami et al, 2008). In addition, the increase in water pH may be associated to the increase in the content of TOC in the soil to a depth of 30 cm, which stimulates H + adsorption, therefore raising the water pH (Hue & Licudine, 1999;Lourenzi et al, 2011).…”
Section: Changes In Soil Acidity Propertiesmentioning
confidence: 97%
“…These changes may also be associated to an increase in soil water pH. The reduction of acidity by manure can also be incremented by the dissociation of CaCO 3, which is usually found in animal excreta (Whalen et al, 2000). As a result of these changes, an increase in the soil effective CEC (CEC effective ) is also to be expected.…”
Section: Introductionmentioning
confidence: 99%
“…Amendments with lime and/or organic matter are commonly used to alter soil pH (Brady and Weil 2010;Whalen et al 2000). Various methods have been proposed to correct soil pH by liming, especially in response to Al toxicity (Dietzel et al 2009).…”
Section: Impacts Of Agricultural Practices On Soil Eh and Phmentioning
confidence: 99%